Nephrocalcinosis: the latest reports on risk factors – a review - Tomasz Dudzik; Łucja Dudzik; Igor Domański; Aleksandra Kozieł; Paulina Wójcik; Natalia Kuderska (Pediatria Polska)
This review synthesizes recent discoveries in the risk factors of nephrocalcinosis, with a particular focus on novel findings. Nephrocalcinosis, characterized by the deposition of calcium salts in the renal parenchyma, is linked to a variety of genetic, metabolic, dietetic, and environmental factors. The study emphasizes the critical role of advanced imaging techniques in diagnosis and the identification of new genetic mutations in genes such as CLCN5, CASR , and SLC34A3 as significant factors contributing to the condition. The paper highlights the importance of recognizing these novel risk factors for better diagnosis, treatment, and prevention of nephrocalcinosis. It calls for further research to explore these new dimensions, particularly the genetic underpinnings and environmental exposures, to develop more effective management strategies and potentially prevent the onset of this complex renal condition.